Food security and nutrition: Growing cities, new challenges - Ruel, Marie T.; Garrett, James L.; Yosef, Sivan (International Food Policy Research Institute, 2017)
Poverty, food insecurity, and malnutrition become increasingly urban problems as urban populations expand everywhere. Persistent child undernutrition, stubborn micronutrient deficiencies, and an alarming rise in overweight and obesity in urban areas mark the shift of the burden of malnutrition from rural areas to cities: One in three stunted children now lives in an urban area. Rapid increases in overweight and obesity have been concentrated in urban areas. The urban poor face a challenging food environment. Food security in the city depends on access to cash. Extremely poor urban households in many developing countries spend more than 50 percent of their budget on food. Dependence on purchased food and employment in the informal sector—especially for women—leave the urban poor vulnerable to income and food price shocks. Formal and informal safety nets often fail to protect the poorest of the urban poor. Limited access to healthcare, safe water, and sanitation in cities leads to severe health and nutrition inequalities for the urban poor—especially slum dwellers.